A GENDER ANALYSIS OF MAIZE MARKETING BY FARMERS IN OYO STATE - Chete, Oluwatoyin (European Scientific Journal, ESJ, 2013)
This study investigates the factors determining the volume of sales of maize by farmers in Oyo State from a gender perspective. A multistage sample of respondents was identified and a regression model estimated. The quantity of maize produced, marital status, household size, farm experience are the significant determinants of volume of maize sales by male farmers, while access to non-farm income, membership of farmers’ association, access to information, household size and farm experience are the significant factors determining maize sales by female farmers. . The government should expose women farmers to information on potential markets and product prices while encouraging them to embrace family planning methods to control the size of their households.